2009
DOI: 10.5012/bkcs.2009.30.12.2913
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the α-Effect in Nucleophilic Substitution Reactions of Y-Substituted Phenyl Benzoates with Butane-2,3-dione Monoximate and Z-Substituted Phenoxides: Ground-State Destabilization vs. Transition-State Stabilization

Abstract: Second-order rate constants (kNu-) have been measured for nucleophilic substitution reactions of Y-substituted phenyl benzoates (1a-i) with butane-2,3-dione monoximate (Ox . Thus, the reactions have been concluded to proceed through a concerted mechanism. Ox -is over 10 2 times more reactive than its reference nucleophile, 4-chlorophenoxide (4-ClPhO -). One might suggest that stabilization of the transition-state (TS) through intramolecular general acid/base catalysis is responsible for the α-effect since such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Variations in the magnitude of the α-effect can be attributed to solvent effects generating differential transition-state stabilization and ground-state destabilization. Depending on the nucleophile–substrate system studied, either transition-state stabilization or ground-state destabilization can dominate as the controlling factor in the overall effect. Differential solvation energies between normal and α-nucleophiles of 16 and 24 kJ mol –1 can lead to ground-state α-effect rate enhancements by factors of 750 and 15000. , Due to this complexity, gas-phase studies provide a vital link to resolving the intrinsic nature of the α-effect and providing insight into solvent effects.…”
Section: Methodsmentioning
confidence: 99%
“…Variations in the magnitude of the α-effect can be attributed to solvent effects generating differential transition-state stabilization and ground-state destabilization. Depending on the nucleophile–substrate system studied, either transition-state stabilization or ground-state destabilization can dominate as the controlling factor in the overall effect. Differential solvation energies between normal and α-nucleophiles of 16 and 24 kJ mol –1 can lead to ground-state α-effect rate enhancements by factors of 750 and 15000. , Due to this complexity, gas-phase studies provide a vital link to resolving the intrinsic nature of the α-effect and providing insight into solvent effects.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that three anions, HOO − , MeOO − , and N 3 − each with an adjacent electron donating group, react particularly fast. The α‐effect has been studied for more than 50 years by experimental and theoretical chemists, and its origin has been rationalized by many theories, but still without a definitive answer. Theories that have been put forward for this effect include: (1) transition state (TS) stabilization, (2) destabilization of the ground state, (3) different solvent effects for normal and α‐Nu, and (4) thermodynamic stability of the product .…”
Section: Introductionmentioning
confidence: 99%
“…The term “α-effect” refers to the abnormal increased reactivity exhibited by nucleophiles (Nu) possessing one or more nonbonding electron pairs at the atom adjacent to the nucleophilic site (these nucleophiles are denoted as α-Nu). The α-effect has been experimentally and theoretically studied for more than 40 years. It was first observed by Jencks and Carriuolo in 1960 in a series of chemical kinetics experiments involving the reaction of the ester p -nitrophenyl acetate with a range of nucleophiles . In 1962, Edwards and Pearson introduced the term α-effect for this anomaly .…”
Section: Introductionmentioning
confidence: 99%
“…In 1962, Edwards and Pearson introduced the term α-effect for this anomaly . Over the years, many theories have been put forward to rationalize this effect, including (1) transition state (TS) stabilization arising from the favorable interaction between an adjacent lone pair and the partial positively charged reaction center in the carbocation; (2) destabilization of the ground state (GS) due to electronic repulsion between the α lone-pair and the nucleophilic electron pair, thereby making the species more reactive; (3) different solvent effects for regular and α-Nu; and (4) thermodynamic stability of the product . However, the true origin of α-effect is still not yet completely understood.…”
Section: Introductionmentioning
confidence: 99%